Prescription Pattern and Costs of Angiotensin II Receptor Blockers in Hypertensive Outpatients - Nurmainah Nurmainah; Nur Anisyah (Pharmacology and Clinical Pharmacy Research)
Angiotensin II receptor blockers (ARBs) have been widely prescribed for primary hypertension. Nevertheless, the cost of ARBs are relatively expensive. The objective of this study was to describe prescribing pattern and the cost of ARBs in hypertensive outpatients. This study used descriptive observational method based on cross-sectional study. Data source was hypertensive outpatients medical records and prescriptions at Pemangkat General Hospital, West Kalimantan, Indonesia, during 2014-2015. The most frequently prescribed anti-hypertensive medication in 1,506 patients were ARBs. There was an increasing trend in the use of ARBs during 2014-2015 (31-38%). The most frequently prescribed ARBs were 8 mg and 18 mg of candesartan, and 80 mg of valsartan. ACE inhibitors were the least prescribed anti-hypertensive drugs (4-8%). The largest portion of anti-hypertensive drugs expenditure was spent on ARBs, both in 2014 and 2015, respectively accounted for IDR 50,493,876.00 (67%) and IDR 58,903,112.00 (79% ). In conclusion, the prescribing of ARBs increased during study period and it represented the largest contributor on total expenditures of anti-hypertensive drugs.Keywords: Angiotensin II receptor blockers, cost, hypertensive patients